Interval Konfidensi untuk Satu Parameter Distribusi Eksponensial di Bawah Sensor Lengkap dengan Metode Bootstrap (Studi Kasus Data Waktu Tunggu Bencana Gempa Bumi di Bulan Maret 2013) - Akhmad Fauzy (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2013)
In this research will be discussed on an interval estimate for the one parameter exponentialdistribution under complete censored data with a case study of data waiting time for earthquakedisaster in March 2013. The exponential distribution has immensely contributed in the analysis oflifetime. Historically the exponential distribution was the first lifetime model in which statisticalmethods in survival analysis were extensively developed. For samples that are singly failure-censoredon the complete censored, confidence intervals on one parameter exponential distribution areobtained from the exact sampling distribution on the following quantity related to the total time ontest T.